Shaft Torsional Vibration Response of Vertical Axis Ocean Current Turbine Model Due to Torque Excitation - Husodo, Adi Wirawan; Utama, I Ketut Aria Pria; Ariana, I Made (Makara Journal of Technology, 2010)
Shaft Torsional Vibration Response of Vertical Axis Ocean Current Turbine Model Due to Torque Excitation. The current research aimed to study the torsional vibration response of Vertical Axis Ocean Current Turbine due to randomly torque excitation pattern, owing to the variety of ocean current velocity. The turbine model is composed of 3 aluminum blades of NACA 0018 connected to steel shaft. Turbine dimensions are 10 cm of chord, 1.8 cm of chamber and 100 cm of span. The variation of ocean current velocity is 0.5 m/s, 1.0 m/s, 1.5 m/s, 2.0 m/s, 2.5 m/s and 3.0 m/s. The Model has 2 degree of freedom which is described into two 2nd order differential equations. The eigenvalue solution yields the model’s natural frequencies; 201,38 rad/s and 457.91 rad/s. Fourier series is used to define the equation of torsional excitation, whilst the vibration equation is solved using Laplace Transform. According to analysis, there is no resonance occur. That because of the system’s natural frequencies is diverse to the magnitude of excitation frequencies. Model will be statically twisted first before vibrated. The response will be transient first then constantly steady. Furthermore, the bigger torque excitation will cause the bigger angular displacement as well the amplitude.